Eradication of Porphyromonas gingivalis Persisters Through Colloidal Bismuth Subcitrate Synergistically Combined With Metronidazole - Wang, Chuan; Li, Xuan; Cheng, Tianfan; Sun, Hongzhe; Jin, Lijian (Frontiers in Microbiology, 2021)
Microbial persisters enable the development of certain intrinsic strategies for survival with extreme tolerance to multiple antimicrobials. Porphyromonas gingivalis is considered to be the “keystone” periodontopathogen. Indeed, periodontitis, as a highly common inflammatory disease, is the major cause of severe tooth loss and edentulism in adults globally, and yet it is crucially involved in various systemic comorbidities like diabetes. We have recently revealed P. gingivalis persisters-induced perturbation of immuno-inflammatory responses and effective suppression of this key pathogen by bismuth drugs. This study further explored novel approaches to eradicating P. gingivalis persisters through synergistic combination of colloidal bismuth subcitrate (CBS) with traditional antibiotics. P. gingivalis (ATCC 33277) cells in planktonic and biofilm states were cultured to stationary phase, and then treated with metronidazole (100 mg/L), amoxicillin (100 mg/L), CBS, (100 μM) and combinations of these medications, respectively. Persister survival rate was calculated by colony-forming unit. Cell viability and cytotoxicity of CBS were assessed in human gingival epithelial cells (HGECs). Notably, CBS combined with metronidazole enabled the effective eradication of P. gingivalis persisters in planktonic mode, and nearly eliminated their existence in biofilm mode. Importantly, CBS exhibited no effects on the viability of HGECs, along with minimal cytotoxicity (<5%) even at a high concentration (400 μM). This pioneering study shows that P. gingivalis persisters could be well eliminated via the synergistic combination of CBS with metronidazole. Our findings may contribute to developing novel approaches to tackling periodontitis and inflammatory systemic comorbidities.